Financial Crisis Management of Business in Eastern Europe in the Context of the Resilience Increase of National Economic Systems - Khatser, Maxim V.; Perehuda, Yuliia A. (Journal of Reviews on Global Economics, 2020)
Motivation: The research has noted great problems of post-Soviet Eastern European countries related to resilience securing of national economic systems, where the defining role belongs to financial crises at the micro-level caused by problems in the development and implementation of financial crisis management. The objective of this research is to study the problems of ensuring the operational efficiency of economic entities in Eastern Europe and to develop a set of measures to increase this efficiency. Novelty: The scientific novelty of the article is a developed set of ways to increase the performance of financial crisis management at the enterprises of post-Soviet Eastern European countries. Methodology and Methods: The methods of data study used in this research represent the quantitative analysis of statistic data. The research has also used the forecasting method of time series, which has suggested using regression functions to forecast future values based on data observed earlier. Data and Empirical Analysis: To conduct the research, data on four Eastern European countries, which were a part of the Soviet Union, for 2008-2018 have been taken. Policy Considerations: Post-Soviet Eastern European countries within the resilience securing of their national economic systems require the development and implementation of ways to increase the performance of financial crisis management at enterprises.